2020
DOI: 10.1177/0301006620914789
|View full text |Cite
|
Sign up to set email alerts
|

Pedestrians Accept Shorter Distances to Light Vehicles Than Dark Ones When Crossing the Street

Abstract: Does the brightness of an approaching vehicle affect a pedestrian’s crossing decision? Thirty participants indicated their street-crossing intentions when facing approaching light or dark vehicles. The experiment was conducted in a real daylight environment and, additionally, in a corresponding virtual one. A real road with actual cars provides high face validity, while a virtual environment ensures the scenario’s precise reproducibility and repeatability for each participant. In both settings, participants ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…The increase of the perceived time-to-arrival supposedly results from a reduction in the perceived speed or, alternatively in the latter case, an increase of the perceived distance. Consistent with these results, pedestrians have been found to accept smaller safety gaps in front of vehicles painted with lighter compared to darker colors (Feldstein & Peli, 2020). As lighter vehicles presented a lower contrast against the well-lit background, this behavior has been attributed to contrast-induced changes in the perceived vehicle kinematics.…”
Section: Introductionsupporting
confidence: 63%
“…The increase of the perceived time-to-arrival supposedly results from a reduction in the perceived speed or, alternatively in the latter case, an increase of the perceived distance. Consistent with these results, pedestrians have been found to accept smaller safety gaps in front of vehicles painted with lighter compared to darker colors (Feldstein & Peli, 2020). As lighter vehicles presented a lower contrast against the well-lit background, this behavior has been attributed to contrast-induced changes in the perceived vehicle kinematics.…”
Section: Introductionsupporting
confidence: 63%
“…In a distance estimation task found no significant differences in estimates of distance in their VR setup compared to the real-world. However, once a motion component was added, judging road crossing safety with a vehicle bearing down on them, different factors influenced people's spatial cognitive perception in VR compared to the real-world (Feldstein and Dyszak, 2020;Feldstein and Peli, 2020). While people demonstrated consistent responses to car color in both scenarios (Feldstein and Peli, 2020), they responded differently to car velocity in the different environments (Feldstein and Dyszak, 2020).…”
Section: Agreement Between Scores On the Real-world And Virtual Reali...mentioning
confidence: 99%
“…However, once a motion component was added, judging road crossing safety with a vehicle bearing down on them, different factors influenced people's spatial cognitive perception in VR compared to the real-world (Feldstein and Dyszak, 2020;Feldstein and Peli, 2020). While people demonstrated consistent responses to car color in both scenarios (Feldstein and Peli, 2020), they responded differently to car velocity in the different environments (Feldstein and Dyszak, 2020). These discrepancies do not preclude the transfer of testing into a virtual world, nevertheless, the different mediums are likely to affect performance, and therefore, the ecological validity of the virtual assessment.…”
Section: Agreement Between Scores On the Real-world And Virtual Reali...mentioning
confidence: 99%
“…In Experiment 2, no effects of reduced contrast where found, indicating that the results of blur were not due to changes in contrast which is in line with a study on time to contact estimations that found no effect of contrast, or luminance levels (Landwehr et al 2013). Yet, a vast amount of studies showing altered velocity perception for moving stimuli with low contrast levels would predict effects on temporal accuracy (Feldstein and Peli 2020;Thompson 1982;Thompson et al 2006). For instance, Battaglini et al (2013) found a main effect of contrast levels on speed perception.…”
Section: Temporal Accuracymentioning
confidence: 99%